Development and psychometric evaluation of the Chinese version of the Participation and Environment Measure for Children and Youth. Issue 15 (16th July 2020) - Chien, Chi-Wen; Li-Tsang, Cecilia W. P.; Cheung, Phoebe Pui Pui; Leung, Ka-Yan; Lin, Chung-Ying
Abstract: Purpose: To adapt the Participation and Environment Measure for Children and Youth for use with Chinese children and youths, and to investigate its psychometric properties. Materials and methods: The Participation and Environment Measure for Children and Youth was translated into Chinese using a cultural adaptation process. Parents of 69 children aged 5–12 years with disabilities and 319 children without disabilities completed the questionnaires. Internal consistency, test-retest reliability, factorial structure, and known-group validity were examined using Cronbach's alpha, intraclass correlation coefficient, confirmatory factor analysis and t -test, respectively. Results: We added and/or replaced activities with culturally-relevant activities in the Chinese version. Internal consistency was acceptable for most of the scales (0.55–0.86). Test-retest reliability of the summary scores was moderate to high (0.70–0.84). Data-model fit was confirmed in a one-factor structure for the participation scales and a two-factor structure for the environment scales. There were also significant differences in the summary scores between 65 gender- and age-matched pairs of children with and without disabilities on the school participation scales and all the environment scales. Conclusion: This study provides psychometric evidence supporting the use of the Participation and Environment Measure for Children and Youth to assess Chinese children's participation and environmental supports/barriers. Implications for rehabilitation: The Chinese version of the Participation and Environment Measure for Children and Youth was developed through a rigorous translation and cultural adaptation process. There is evidence for the reliability (internal consistency and test-retest reliability) and construct validity (factorial structure and known-group validity) of the Chinese version of the Participation and Environment Measure for Children and Youth. The Chinese version of the Participation and Environment Measure for Children and Youth can be used to assess children's participation in home, school and community settings and to identify environmental barriers that require further intervention.